Answer:
Daniel (now) is 3 years old, (2 years ago) is 1 year old.
Kevin (now) is 6 years old, (2 years ago) is 4 years old.
Step-by-step explanation:
Now:
-Kevin: k = d + 3
-Daniel: d
2 years ago:
-Kevin: k - 2 = 4(d - 2)
-Daniel: d - 2
We have the equation:
(k - 2) + 2 = k
4(d - 2) + 2 = d + 3
4d - 8 + 2 = d + 3
3d - 6 = 3
3d = 9
d = 3
k = d + 3 = 3 + 3 = 6
Answer:
2.7g/cm^3
step-by-step explanation:
Answer:
It would be B. Mr. Connor would drive 207 miles altogether on Monday and Tuesday! :)
Step-by-step explanation:
Add 129 + 78 = ???
Hey there!
These are technically expressed as fraction. When you divide a fraction by another, you can replace the second fraction with its reciprocal and you can now multiply the fractions together instead.
![\frac{x^2-x-12}{2x^2} / \frac{x^2+x-6}{2x^3}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2-x-12%7D%7B2x%5E2%7D%20%2F%20%20%5Cfrac%7Bx%5E2%2Bx-6%7D%7B2x%5E3%7D)
![\frac{x^2-x-12}{2x^2} * \frac{2x^3}{x^2+x-6}](https://tex.z-dn.net/?f=%5Cfrac%7Bx%5E2-x-12%7D%7B2x%5E2%7D%20%2A%20%5Cfrac%7B2x%5E3%7D%7Bx%5E2%2Bx-6%7D)
Now, just multiply across the top and the bottom. You can first cancel out any terms that are repeated or similar.
![\frac{12}{2x^2} * \frac{2x^3}{-6}](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B2x%5E2%7D%20%2A%20%5Cfrac%7B2x%5E3%7D%7B-6%7D)
![\frac{2}{x} * \frac{1}{-1}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bx%7D%20%2A%20%5Cfrac%7B1%7D%7B-1%7D)
![\frac{2}{-x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B-x%7D)
Your answer will be
![\frac{2}{-x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B-x%7D)
.
Hope this helped you out! :-)